Scientific Literacy-Based Chemical Teaching Materials Design of Chemical Solution Materials on Sea Pollution Context - Nurul Asikin; Inelda Yulita (Postgraduate, University of Mataram, 2019)
Abstract: The science teaching materials needed today are teaching materials that can make students literate in science. One way is to develop teaching materials based on scientific literacy. To produce good teaching materials, certain designs are needed to achieve learning goals and can improve students' scientific literacy. Students who have studied chemistry should be able to analyze natural phenomena in scientific chemistry, one of which is marine pollution. This research was conducted to design high school chemistry teaching materials in connecting the context of sea pollution with chemical solution material. The method of this research is descriptive qualitative which refers to the Model of Educational Reconstruction (MER). The instruments used were standard competencevalidation sheets, text analysis sheets, and teaching material validation sheets. The results showed: a) The results of the indicator standard competencevalidation and learning objectives cognitive and attitude aspects, the results of text analysis and the results of the validation of teaching materials, all obtained valid categories, with the average value of each CVI was 0.91; 0.93; 0.94; and 0.95, b) The design of teaching materials include the contact stage, the curriculum stage, the elaboration stage, the decision-making stage, and the Nexus stage. Keywords:Design of teaching materials; scientific literacy; sea pollution; chemical solution